PENGGUNAAN ICE BREAKING UNTUK MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK DI SEKOLAH DASAR - Taufiqulloh Dahlan; Acep Roni Hamdani; Aas Saraswati; Dadang Iskandar; Cica Yulia Putri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The lack of motivation to learn leads to students showing less enthusiasm in their learning process. Therefore, the author is interested in implementing the Ice Breaking technique. The main objective of this study was to examine the impact of the applied Ice Breaking technique. The research adopted a quasi-experimental approach and was conducted at SD Negeri 255 Griya Bumi Antapani, Bandung City, targeting third-grade students with a total population of 105. The sampling method employed was purposive sampling, where 20 students each were selected from both Class III-B (control group) and Class III-C (experimental group), resulting in a total of 40 students in both control and experimental classes. The results of the homogeneity test indicated that there were homogeneous data variants and samples after the treatment. Data for the study were collected using a questionnaire. The findings of the research revealed the following: There is a significant influence of using the Ice Breaking technique on the learning motivation of third-grade students at SD Negeri 255 Griya Bumi Antapani, Bandung City, during the 2021/2022 academic year. This conclusion is supported by the outcomes of the Independent Sample T Test, which showed a Sig. (2-tailed) value of 0.000, indicating that it is less than 0.05. As a result, the null hypothesis (Ho) was rejected, and the alternative hypothesis (Hα) was accepted. The average motivation score of the experimental class was 81.60, which is higher than the control class's average score of 61.75.